Early detection of risk of reading difficulties using a working memory assessment battery. (30th June 2022) - Atkinson, Susan J.; Martin, Colin R.
Abstract: Research suggests a role for aspects of the working memory system in reading. While much of the evidence points to a role for working memory capacity and the phonological loop, more recent work indicates a role for the central executive component, although findings remain unclear. There is an identified need for a reliable screening measure for risk of reading difficulties in children who are pre‐readers. Recent research suggests that working memory measures may contribute to such a measure in addition to existing tests of phonological ability, non‐verbal reasoning, motor skills and language. One hundred and two children aged between 56 and 69 months were assessed on measures of reading accuracy, working memory capacity, processing speed and a range of measures designed to assess central executive functioning. Linear regression, discriminant function analysis and confirmatory factor analysis were conducted to determine the predictive qualities and factor structure of the working memory assessment battery. Discriminant function analysis indicated that the working memory assessment battery was able to significantly discriminate between children who were at risk and not at risk of reading difficulties (as indicated by an independent measure). Linear regression and Confirmatory Factor Analysis revealed that the tests were a good predictor of the later outcome, particularly the alliteration fluency and sentence verification tasks. Therefore, the working memory assessment battery promises to be a useful screening measure for potential reading difficulties in educational settings, facilitating early effective intervention.